Phosphoproteomic analysis of anaplastic lymphoma kinase (ALK) downstream signaling pathways identifies signal transducer and activator of transcription 3 as a functional target of activated ALK in neuroblastoma cells. (22nd August 2013) - Sattu, Kamaraj; Hochgräfe, Falko; Wu, Jianmin; Umapathy, Ganesh; Schönherr, Christina; Ruuth, Kristina; Chand, Damini; Witek, Barbara; Fuchs, James; Li, Pui‐Kai; Hugosson, Fredrik; Daly, Roger J.; et al.
<x xml:space="preserve">Abstract</x> Activation of the anaplastic lymphoma kinase (ALK) receptor tyrosine kinase is a key oncogenic mechanism in a growing number of tumor types. In the majority of cases, ALK is activated by fusion with a dimerizing partner protein as a result of chromosomal translocation events, most studied in the case of the nucleophosmin–ALK and echinoderm microtubule‐associated protein‐like 4–ALK oncoproteins. It is now also appreciated that the full‐length ALK receptor can be activated by point mutations and by deletions within the extracellular domain, such as those observed in neuroblastoma. Several studies have employed phosphoproteomics approaches to find substrates of ALK fusion proteins. In this study, we used MS‐based phosphotyrosine profiling to characterize phosphotyrosine signaling events associated with the full‐length ALK receptor. A number of previously identified and novel targets were identified. One of these, signal transducer and activator of transcription 3 (STAT3), has previously been observed to be activated in response to oncogenic ALK signaling, but the significance of this in signaling from the full‐length ALK receptor has not been explored further. We show here that activated ALK robustly activates STAT3 on Tyr705 in a number of independent neuroblastoma cell lines. Furthermore, knockdown of STAT3 by RNA interference resulted in a reduction in myelocytomatosis neuroblastom (MYCN) protein levels downstream of ALK signaling. These observations, together with a decreased level of MYCN and inhibition of neuroblastoma cell growth in the presence of STAT3 inhibitors, suggest that activation of STAT3 is important for ALK signaling activity in neuroblastoma.